ANALYSIS OF SHARIA INNOVATION STRATEGIC AND EFFICIENCY TOWARD SUSTAINABLE ABILITY SHARIAH MANDIRI BANKS IN LAMPUNG - Andri, Andri; Suryanto, Tulus; Ghofur, Ruslan Abdul; Anggraeni, Erike (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
This study aims to reveal the influence of factors that influence the ability of 'sustainable banks' in facing threats from the internal and external environment, especially financial technology. The novelty of this article lies in the discovery of research results that provide a complex development model in the strategy of Islamic financial institutions in maintaining sustainable capability. Quantitative research methods with Islamic economics approach are chosen to answer the research hypotheses. The 30 sample respondents consisting of Branch Managers and Senior Employees from branch offices and sub-branch offices of the Bank Syariah Mandiri (BSM) Lampung Province are potential primary data used. The results revealed that there was a positive and significant effect of 80.6% between sharia innovation and efficiency on the sustainability of Bank Syariah Mandiri in Lampung Province. While the remaining 18.4% is influenced by other variables not examined in the study. In creating new innovations and efficiencies, BSM Lampung Province must always be in the corridors of Islamic principles as rahmatan lil alamin.Keywords: Bank, Efficiency, Innovation, Sharia, Sustainability